How do Competitive and Regulatory Pressures Interact with Internal Corporate Governance?: Evidence from the Cameroonian Banking Sector (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The objective of this article is to analyse the impact of both external and internal mechanisms of corporate governance on banks performance in Cameroon. The internal governance mechanisms consist of those linked with the Board of directors (its size and composition) and the ownership structure (ownership concentration, equity capital of each type of shareholder). External mechanisms consist of pressure from competitors, and regulatory pressure from the banking Commission following the adoption of equity principles or rules. Research carried out on a sample of 11 Cameroonian banks showed the effect of complementarity between the control exerted by internal stakeholders (institutional shareholders, insiders ownership, size of the Board of directors) and competitive pressure. On the contrary, a substitution effect was detected between State administrators and competitive pressure. Results obtained also revealed the substitution effect between control exercised by the Board of directors and regulatory pressure.